2001
DOI: 10.1002/1096-9896(200107)194:3<349::aid-path887>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Microarrays of bladder cancer tissue are highly representative of proliferation index and histological grade

Abstract: The number of genes suggested to play a role in cancer biology is rapidly increasing. To be able to test a large number of molecular parameters in sufficiently large series of primary tumours, a tissue microarray (TMA) approach has been developed where samples from up to 1000 tumours can be simultaneously analysed on one glass slide. Because of the small size of the individual arrayed tissue samples (diameter 0.6 mm), the question arises of whether these specimens are representative of their donor tumours. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
2
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(158 citation statements)
references
References 23 publications
6
145
2
4
Order By: Relevance
“…Tissue microarray studies have almost always reproduced the expected biological relevance of a given biomarker, for example, the clinical significance of Ki-67 labeling index in bladder cancer, the prognostic role of steroid hormone receptor expression and Her2 neu amplification/overexpression in breast cancer as well as many other established or new associations between molecular markers and tumor phenotype or clinical outcome. 41,45,48 Also in our study, there was a high concordance of tissue microarray results and data obtained on large tissue specimens. Previous studies have found calretinin positivity in 50-100% of epithelioid malignant mesothelioma, with only very few studies showing expression frequencies below 90% on large tissue sections.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Tissue microarray studies have almost always reproduced the expected biological relevance of a given biomarker, for example, the clinical significance of Ki-67 labeling index in bladder cancer, the prognostic role of steroid hormone receptor expression and Her2 neu amplification/overexpression in breast cancer as well as many other established or new associations between molecular markers and tumor phenotype or clinical outcome. 41,45,48 Also in our study, there was a high concordance of tissue microarray results and data obtained on large tissue specimens. Previous studies have found calretinin positivity in 50-100% of epithelioid malignant mesothelioma, with only very few studies showing expression frequencies below 90% on large tissue sections.…”
Section: Discussionsupporting
confidence: 82%
“…Tissue microarrays have proven highly representative in comparison with traditional evaluation through methods on large tissue samples. [40][41][42][43][44][45][46][47][48][49][50][51] …”
mentioning
confidence: 99%
“…The tissue microarray technique is an accepted tool of investigation, especially when a huge number of samples are analyzed. 18,[23][24][25][26][27][28] The randomization of the study population into two subgroups allowed us to determine the best cutoffs for cytoplasmic and nuclear Mst1 expression on the first subgroup (N ¼ 599) based on the ROC curve analysis and to apply the determined cutoffs on the second subgroup (N ¼ 598) as well as on the third group (N ¼ 141). This approach has the important advantage of avoiding a scoring system that includes a subjectively selected cutoff or a complex composite scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…The application of tissue microarrays represents a highthroughput approach for validation of potential novel markers for bladder cancer by immunohistochemistry or in situ hybridisation in paraffin blocks (Kononen et al, 1998;Schraml et al, 1999;Richter et al, 2000;Nocito et al, 2001). Several reports describe the rapid evaluation of targets of interest, such as cytoskeletal actinassociated gelsolin or E-cadherin (Rao et al, 2002), Na,K-ATPase or cell-cycle-related markers (Espineda et al, 2003).…”
Section: Bladder Cancer Studies Using Clinical Specimensmentioning
confidence: 99%